Liner Production of Florida Native Wildflowers by Seed - Jeffrey G. Norcini; James H. Aldrich (EDIS, 2008)
ENH-1087, a 4-page illustrated fact sheet by Jeffrey G. Norcini and James H. Aldrich, describes in detail the methods that the authors have successfully used to produce liners of Florida native wildflowers under greenhouse conditions. Includes references. Published by the UF Department of Environmental Horticulture, December 2007.